Effects of Fresh Corn Stover to Corn Flour Ratio on Fermentation Quality and Bacterial Community of Mixed Silage - Jintong Li; Ke Wu; Jiaxuan Wu; Chuang Yang; Baoli Sun; Ming Deng; Dewu Liu; Yaokun Li; Guangbin Liu; Yongqing Guo (Fermentation)
Due to the high price of whole-plant corn silage in southern China, many dairy farms are attempting to prepare whole-plant corn silage using corn stover and corn flour, but the mixing ratio has not yet been determined. Therefore, we mixed fresh corn stover and corn flour at the proportions of 100:0 (F0 group) to 80:20 (F20 group), using five groups with three replicates each. The optimal mixing ratio was determined by assessing the nutritional composition, fermentation quality, and bacterial community of silage after 45 days. The results showed that dry matter and water-soluble carbohydrates in silage increased linearly with the increasing ratio of corn flour (p < 0.01) while crude protein, true protein, neutral detergent fiber, acidic detergent fiber, and crude ash content decreased linearly (p < 0.01). The F0 group had the highest pH, and the mixing ratio quadratically affected ammonia nitrogen concentration (p < 0.05). Additionally, at the phylum level, the relative abundances of Proteobacteria and Cyanobacteria in the F15 group were significantly higher than in other groups (p < 0.05). At the genus level, Lactobacillus increased with corn flour inclusion compared to the F0 group. In conclusion, the silage quality is the best when the mixing ratio of fresh corn stover and corn flour is 85:15.